An Integrated Inventory-Transportation System with Periodic Pick-Ups and Leveled Replenishment - Thomas Volling; Martin Grunewald; Thomas S. Spengler (BuR - Business Research, 2013)
In this paper we develop a combined inventory-transportation system. The general idea is to integrate a simple replenishment policy with a routing component to derive operationally consistent standard routes as a basis for milk run design. The most interesting feature of the approach is that we combine stochastic vehicle routing with a replenishment policy which makes use of inventory to level the variability propagated into transportation operations. To evaluate the approach, we compare its performance with stochastic vehicle routing as well as sequential vehicle routing and replenishment planning. With respect to these approaches, substantial gains are achieved.
urn:nbn:de:0009-20-38096
Keywords: 650; inbound logistics; inventory routing; milk run design